Impact Of Location Decision On Patronage Of Eateries In Ilorin Metropolis, Kwara State, Nigeria - Emmanuel Olaniyi Dunmade (Indonesian Journal Of Business And Economics, 2022)
The eatery business operation in Nigeria is now facing heavy competition simply because of the growing number of eateries in the country, where restaurants spring up nearly every week. This spread is not unrelated to the general increase in social and economic activity and the entrepreneurial tendency of university graduates in the face of rising unemployment. Despite the alleged acceptance of eateries in Nigeria, however, consumers are now being selective at these eateries' locations. Thus, this paper examined impact of location decision on patronage of eateries in Ilorin metropolis. To this end, cross sectional survey method was adopted, while twenty functional eatery outlets were purposely selected and 355 customers of the selected eateries were sampled. Primary data were sourced through questionnaire and the hypotheses tested using regression analysis with the aid of SPSS (version 22.0). The results indicate that the R-square value was 0.722 (72.2%) posits that the two independent variables of proximity of eatery location and convenient accessibility of eatery location contribute to variation in the dependent variables. The study concluded that eatery location has significant effect on customer repeating purchases. Thus, management of eatery business must be strategic in making location policies, which must conform to the needs and preferences of the customers so as to maximize customer’s patronage as could be seen in increased sales and marginal profit.